Ampullary carcinoma: effect of preoperative biliary drainage on surgical outcome - Abdullah, Sheikh Anwar; Gupta, Tarun; Jaafar, Khairul Azhar; Chung, Yaw Fui Alexander; Mesenas, Steven Joseph; London, Lucien Peng Jin Ooi (Baishideng Publishing Group, 2009)
AIM: To evaluate the influence of preoperative biliary drainage on morbidity and mortality after surgical resection for ampullary carcinoma. METHODS: We analyzed retrospectively data for 82 patients who underwent potentially curative surgery for ampullary carcinoma between September 1993 and July 2007 at the Singapore General Hospital, a tertiary referral hospital. Diagnosis of ampullary carcinoma was confirmed histologically. Thirty-five patients underwent preoperative biliary drainage (PBD group), and 47 were not drained (non-PBD group). The mode of biliary drainage was endoscopic retrograde cholangiopancreatography (n = 33) or percutaneous biliary drainage (n = 2). The following parameters were analyzed: wound infection, intra-abdominal abscess, intra-abdominal or gastrointestinal bleeding, septicemia, biliary or pancreatic leakage, pancreatitis, gastroparesis, and re-operation rate. Mortality was assessed at 30 d (hospital mortality) and also long-term. The statistical endpoint of this study was patient survival after surgery. RESULTS: The groups were well matched for demographic criteria, clinical presentation and operative characteristics, except for lower hemoglobin in the non-PBD group (10.9 ± 1.6 vs 11.8 ± 1.6 in the PBD group). Of the parameters assessing postoperative morbidity, incidence of wound infection was significantly less in the PBD than the non-PBD group [1 (2.9%) vs 12 (25.5%)]. However, the rest of the parameters did not differ significantly between the groups, i.e. sepsis [10 (28.6%) vs 14 (29.8%)], intra-abdominal bleeding [1 (2.9%) vs 5 (10.6%)], intra-abdominal abscess [1 (2.9%) vs 8 (17%)], gastrointestinal bleeding [3 (8.6%) vs 5 (10.6%)], pancreatic leakage [2 (5.7%) vs 3 (6.4%)], biliary leakage [2 (5.7%) vs 3 (6.4%)], pancreatitis [2 (5.7%) vs 2 (4.3%)], gastroparesis [6 (17.1%) vs 10 (21.3%)], need for blood transfusion [10 (28.6%) vs 17 (36.2%)] and re-operation rate [1 (2.9%) vs 5 (10.6%)]. There was no early mortality in either group. Median survival was 44 mo (95% CI: 34.2-53.8) in the PBD group and 41 mo (95% CI: 27.7-54.3; P = 0.86) in the non-PBD group. CONCLUSION: Biliary drainage before surgery for ampullary cancer significantly reduced postoperative wound infection. Overall mortality was not influenced by preoperative drainage.